Analysis of Service Quality on Customer Satisfaction Through Importance Performance Analysis and KANO Model - Nurul Ummi; Nuraida Wahyuni; Iqbhal Apriadi (Journal Industrial Servicess, 2021)
Customer satisfaction is the level at which the perceived performance of the product will match the expectations of a customer. PT. Astra International Tbk-Daihatsu is a company that runs in the automotive field This study was conducted in the workshop division because it has a very high target in the customer satisfaction index which is 93. In addition, the failure of reaching the customer satisfaction index target in March represents the gap between customers and the company’s service. Also, the employees in the workshop service and spare parts get a warning in the form of a warning letter and income reduction in that period. The purpose of this research is to know the service attributes that need to be improved based on the integration of the Importance Performance Analysis (IPA) method and the KANO model. The results of this study show that in the IPA model there are 2 quadrants containing attributes that must be improved. Quadrant I is the main priority consisting of attribute 1, attribute 5, attribute 9, and attribute 11. On the other hand, the KANO model results in 3 attribute categories namely attractive consisting of attribute 1, attribute 2, attribute 7, attribute 9, then one dimensional consisting of attribute 3, attribute 4, attribute 5, attribute 6, attribute 8, attribute 10, attribute 11, attribute 12, attribute 14, attribute 15, attribute 16, attribute 17, attribute 18, attribute 19, attribute 20, and the last must be consisting of attribute 13. Furthermore, integration between the IPA and KANO models is carried out to produce service priorities that must be improved. From the results of the integration, it is found that the service attributes that are the priority for improvement are attribute 1, attribute 5, attribute 9, attribute 11, attribute 7, attribute 3 and attribute 14.